The neglected ones: Time at home during COVID-19 and child maltreatment. (December 2021) - Bullinger, Lindsey Rose; Raissian, Kerri M.; Feely, Megan; Schneider, William J.
Highlights: COVID-19 led to parents navigating a new landscape without their usual supports. We combine early release child maltreatment reports with unique mobile phone data. Children in areas staying home more were more likely to be reported for maltreatment. Reports in these areas were more likely to be substantiated, particularly neglect. Increases in substantiated cases of maltreatment was only in metropolitan counties. Abstract: The early months of the COVID-19 pandemic led to extreme social isolation, precarious employment and job loss, working from home while tending to children, and limited access to public services. The confluence of these factors likely affects child health and well-being. We combine early release child maltreatment reports in Indiana with unique and newly available mobile phone movement data to better understand the relationship between staying at home intensively during the COVID-19 pandemic and child maltreatment. Our findings indicate that the prolonged stays at home promoted by the early public health response to COVID-19 resulted in reductions in child maltreatment reports overall and substantiated reports of maltreatment. However, relative to areas that stayed home less, children in areas that stayed home more were more likely to be both reported for and a confirmed victim of maltreatment, particularly neglect. These areas have historically been socioeconomically advantaged and experienced lower rates of maltreatment. We only observe increases in confirmed child maltreatment in metropolitan counties, suggesting that the effects of staying home on child maltreatment may reflect both the differential risk of leaving home and access to services in metropolitan–rather than non-metropolitan–counties. Staying at home has been challenging for many families. Families likely need assistance as the pandemic persists, evolves, and when it ends.